Evidence‐based practice: the use and abuse of research. Issue 1 (5th February 2023) - Imray, Peter; Kossyvaki, Lila; Sissons, Mike
Abstract : The authors of this position paper argue that there is currently very little evidence‐based practice in relation to learners with severe learning disabilities (SLD) and profound and multiple learning disabilities (PMLD), and that which there is, has often been badly used and/or abused. More specifically, we argue that relevant educational research undertaken so far has a strong tendency towards: (i) conflating the need for common strategies to be universally used in teaching, with the 'need' for a common curriculum; (ii) quoting research that applies to children with certain types of SEND as though it applies to all children with SEND; (iii) assuming there is a homogeneity of learning disability among people with the same condition (for example Down's syndrome, autism) and (iv) encouraging assumptions that any academic progress, no matter how small the gain, is axiomatically superior in value for all pupils. The authors conclude that there is need for a new look at 'evidence‐based practice' for these populations.